Perception and practice of breastfeeding among HIV positive mothers receiving care for prevention of mother to child transmission in South-East, Nigeria - Ancilla-Kate Umeobieri; Chinyere Mbachu; Benjamin S. C. Uzochukwu; Aniwada Elias; Babatunde Omotowo; Chuka Agunwa; Ikechukwu Obi (BMC, 2018)
Abstract Background Although the risk of HIV transmission through breastfeeding is reduced considerably with the use of antiretroviral therapy, infant feeding by HIV positive mothers remains controversial. Weighing risks against benefits generates intense debate among policymakers, program managers and service providers in sub-Saharan Africa, considering that the major causes of infant death of malnutrition and infectious diseases, could be prevented if mothers breastfeed their babies. Whereas breastfeeding involves some risk of HIV transmission, not breastfeeding poses considerable risk to infant survival. This study investigated perceptions and practice of breastfeeding of HIV-exposed infants among HIV positive mothers. Methods A cross-sectional descriptive study was conducted in Enugu metropolis among HIV positive mothers receiving care for prevention of mother-to-child transmission of HIV from two public and two private hospitals. Interviewer-administered questionnaire survey was done with 550 participants as they exited the final point of service delivery. Descriptive statistics of perception and practice variables and cross tabulation of selected variables was performed. Results Most mothers knew that HIV could be transmitted through breast milk. The majority perceived any type of breastfeeding as beneficial to the infant: 230 (83.6%) in private facilities, and 188 (68.4%) public facilities. Over three-quarters of the mothers breastfed their infants and their reasons for breastfeeding included personal choice, cultural norms, fear of HIV status being disclosed and pressure from family members. A statistical significant association was found between; (i) practice of breastfeeding and marital status, (p < 0.01), and (ii) practice of breastfeeding and household income provider (p = 0.02). However, neither marital status (AOR 1.4; 95% CI 0.3, 6.8) nor being the household income provider (AOR 4.9; 95% CI 0.6, 12.9) is a significant predictor of breastfeeding of HIV-exposed infants. Conclusions Breastfeeding remains a common trend among HIV positive women and it is associated with economic independence of women and social support. Fear of stigma negatively affects practice of breastfeeding. Hence, HIV positive mothers need economic independence and the support of family members to practice recommended infant feeding options.